Comparing transverse momentum balance of b jet pairs in pp and PbPb collisions at √sNN=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
The transverse momentum balance of pairs of back-to-back b quark jets in PbPb and pp collisions recorded with the CMS detector at the LHC is reported. The center-of-mass energy in both collision systems is 5.02 TeV per nucleon pair. Compared to the pp collision baseline, b quark jets have a larger imbalance in the most central PbPb collisions, as expected from the jet quenching effect. The data are also compared to the corresponding measurement with inclusive dijets. In the most central collisions, the imbalance of b quark dijets is comparable to that of inclusive dijets